Exoproteome Analysis of the Seaweed Pathogen Nautella italica R11 Reveals Temperature-Dependent Regulation of RTX-Like Proteins - Gardiner, Melissa; Bournazos, Adam M.; Maturana-Martinez, Claudia; Zhong, Ling; Egan, Suhelen (Frontiers in Microbiology, 2017)
Climate fluctuations have been linked to an increased prevalence of disease in seaweeds, including the red alga Delisea pulchra, which is susceptible to a bleaching disease caused by the bacterium Nautella italica R11 under elevated seawater temperatures. To further investigate the role of temperature in the induction of disease by N. italica R11, we assessed the effect of temperature on the expression of the extracellular proteome (exoproteome) in this bacterium. Label-free quantitative mass spectrometry was used to identify 207 proteins secreted into supernatant fraction, which is equivalent to 5% of the protein coding genes in the N. italica R11 genome. Comparative analysis demonstrated that expression of over 30% of the N. italica R11 exoproteome is affected by temperature. The temperature-dependent proteins include traits that could facilitate the ATP-dependent transport of amino acid and carbohydrate, as well as several uncharacterized proteins. Further, potential virulence determinants, including two RTX-like proteins, exhibited significantly higher expression in the exoproteome at the disease inducing temperature of 24°C relative to non-inducing temperature (16°C). This is the first study to demonstrate that temperature has an influence exoproteome expression in a macroalgal pathogen. The results have revealed several temperature regulated candidate virulence factors that may have a role in macroalgal colonization and invasion at elevated sea-surface temperatures, including novel RTX-like proteins.